2016
DOI: 10.1523/jneurosci.0311-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Transient Modulations of Neural Responses to Heartbeats Covary with Bodily Self-Consciousness

Abstract: Recent research has investigated self-consciousness associated with the multisensory processing of bodily signals (e.g., somatosensory, visual, vestibular signals), a notion referred to as bodily self-consciousness, and these studies have shown that the manipulation of bodily inputs induces changes in bodily self-consciousness such as self-identification. Another line of research has highlighted the importance of signals from the inside of the body (e.g., visceral signals) and proposed that neural representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
132
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 51 publications
10
132
0
Order By: Relevance
“…Linking back to the "pins and needles" sensation reported by participants, physiological reactions to the illusion should be investigated following previous protocols on the RHI (body temperature (Macauda et al, 2015;G. L. Moseley et al, 2008), nociception (Hansel et al, 2011;Romano et al, 2014), cardiac signalling (Park et al, 2016), response to threat (H. Henrik Ehrsson et al, 2007), and immunological responses (Barnsley et al, 2011)) up to high-level cognition (Maister et al, 2015)).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linking back to the "pins and needles" sensation reported by participants, physiological reactions to the illusion should be investigated following previous protocols on the RHI (body temperature (Macauda et al, 2015;G. L. Moseley et al, 2008), nociception (Hansel et al, 2011;Romano et al, 2014), cardiac signalling (Park et al, 2016), response to threat (H. Henrik Ehrsson et al, 2007), and immunological responses (Barnsley et al, 2011)) up to high-level cognition (Maister et al, 2015)).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This phenomenological experience of ownership over the rubber hand is accompanied by objectively-measurable changes in a broad variety of processes ranging from basic physiological mechanisms (e.g., body temperature (Macauda et al, 2015;G. L. Moseley et al, 2008), nociception (Hansel, Lenggenhager, von Kanel, Curatolo, & Blanke, 2011;Romano, Pfeiffer, Maravita, & Blanke, 2014), cardiac signalling (Park et al, 2016), response to threat (H. Henrik Ehrsson, Wiech, Weiskopf, Dolan, & Passingham, 2007), and immunological responses (Barnsley et al, 2011)) up to high-level cognition (see e.g. (Maister, Slater, Sanchez-Vives, & Tsakiris, 2015) for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 79 subjects with normal or corrected to normal vision were recruited to participate. of previous studies 85,86 . Power analysis indicated that 16 participants are sufficient to perform a parametric analysis with a power of 0.8 (previous BSC studies).…”
Section: Subjectsmentioning
confidence: 55%
“…The region most reliably contributing to the HER difference between self and other in this task was the posteromedial cortex. The most ventral portion of this region, encompassing the posterior cingulate cortex, within the default network (Andrews--Hanna et al, 2014), has previously been shown to elicit HERs in relation to the self--relatedness of spontaneous thoughts (Babo--Rebelo et al, 2016a, 2016b) and bodily self--consciousness (Park et al, 2016). Evidence is thus now converging to support the idea of an integrative role of the posterior cingulate cortex, between self--related cognitive processes Qin and Northoff, 2011;Vogt and Laureys, 2005) and physiological functions such as cardiac monitoring.…”
Section: The Posteromedial Cortex Generates the Her Difference Betweementioning
confidence: 99%
“…Experimentally, heartbeat--evoked responses (HERs), i.e. transient changes in brain activity locked to heartbeats, were shown to encode the degree of self--relatedness of spontaneous thoughts (Babo--Rebelo et al, 2016a, 2016b and were associated with different aspects and levels of bodily self--consciousness (Park et al, 2016;Sel et al, 2016). These results suggest a link between the neural monitoring of the heart and selfhood, such that the brain would refer to internal bodily signals, in particular the heart, to tag mental processes as being self--related.…”
Section: Introductionmentioning
confidence: 99%